Carbonate system of surface sediments from the South Pacific - Franziska Kersten; Ralf Tiedemann; Jan Fietzke; Matthias Frische (PANGAEA, 2013)
B/Ca ratios in Cibicides mundulus and Cibicides wuellerstorfi have been shown to correlate with the degree of calcite saturation in seawater (D[CO32-]). In the South Pacific, a region of high importance in the global carbon cycle, these species are not continuously present in down-core records. Small numbers of epibenthic foraminifera in samples present an additional challenge, which can be overcome by using laser ablation-inductively coupled-mass spectrometry (LA-ICP-MS). We present a laser ablation based core-top calibration for Cibicides cf. wuellerstorfi, a C. wuellerstorfi morphotype that is abundant in the South Pacific and extend the existing global core top calibration for C. mundulus and C. wuellerstorfi to this region. B/Ca in C. cf. wuellerstorfi are linearly correlated with D[CO32-] and possibly display a higher sensitivity to calcite saturation changes than C. wuellerstorfi. Trace element profiles through C. wuellerstorfi and C. mundulus reveal an intra-shell B/Ca variation of ±36% around the mean shell value. Mg/Ca and B/Ca display opposite trends along the shell. Both phenomena likely result from ontogenetic effects. Intra-shell variability equals intra-sample variability, mean sample B/Ca values can thus be reliably calculated from averaged spot results of single specimen. In the global B/Ca-D[CO32-] range, we observe an inverse relationship between water mass age and D[CO32-].
Supplement to: Kersten, F et al. (2013): The B/Ca proxy for past seawater carbonate chemistry reconstructions-laser ablation based calibrations for C. mundulus, C. wuellerstorfi and its morphotype C. cf. wuellerstorfi. Climate of the Past Discussions, 9(4), 4425-4448, https://doi.org/10.5194/cpd-9-4425-2013